The big crew change - NICHOLLS, Tom (Petroleum Economist, 2006)
Oil executives increasingly recognise that effective recruitment and human-resources management are as vital to the continuing success of the oil industry as any other aspect of the business. Recruitment was one of the main subjects in a speech delivered last month by Shell's chief executive, Jeroen van der Veer, on the theme of how energy will be supplied in the future. According to research by the Booz Allen Hamilton consultancy, around 50% of professional exploration and production staff are aged 40-50, while only around 15% are in their early 20s to mid-30s. BAH says up to half of the workforce should retire within 10 years and that technical segments of the industry are likely to suffer most. At the same time, demands on energy suppliers have never been greater. Total demand for energy worldwide - most of it for oil, gas and coal - increased by 15% in the first five years of this century alone. Some estimates suggest 200 million new customers for commercial energy are added every year. Consequently, energy companies need more manpower than ever and are hiring in record numbers.